2012
DOI: 10.1155/2012/146463
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to RHAMM in Patients with Acute Myeloid Leukemia after Chemotherapy and Allogeneic Stem Cell Transplantation

Abstract: Leukemic blasts overexpress immunogenic antigens, so-called leukemia-associated antigens like the receptor for hyaluronan acid-mediated motility (RHAMM). Persistent RHAMM expression and decreasing CD8+ T-cell responses to RHAMM in the framework of allogeneic stem cell transplantation or chemotherapy alone might indicate the immune escape of leukemia cells. In the present study, we analyzed the expression of RHAMM in 48 patients suffering from acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…MLPC was performed as described elsewhere . Briefly, specific CD8+ T cells were positively selected by magnetic‐activated cell sorting (MACS) columns (MiltenyiBiotec, Bergisch‐Gladbach, Germany).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MLPC was performed as described elsewhere . Briefly, specific CD8+ T cells were positively selected by magnetic‐activated cell sorting (MACS) columns (MiltenyiBiotec, Bergisch‐Gladbach, Germany).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…The frequency of WT1‐specific T cells was determined by flow cytometry. Tetramer staining was performed as described previously . Briefly, lymphocytes were stained with WT1‐specific tetramers and posterior with conjugated antibodies to CD3 and CD8 (BD Biosciences).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…Thus, TCR-transgenic lymphocytes specific for RHAMM limit tumor outgrowth in vivo in various solid and leukemia tumor models [137]. It has been suggested that immunotherapies like peptide vaccination or adoptive transfer of RHAMM-specific T cells might improve the immune response and the outcome of acute myeloid leukemia patients [138]. Moreover, it has been shown in vivo that sulfated hyaluronan augmented tumor growth due to a blockade in complex formation between phosphoinositide 3-kinase (PI3K) and hyaluronan receptors and to a transcriptional downregulation of HA receptors, CD44, and RHAMM, along with PI3K inhibition [139].…”
Section: The Role Of Rhamm In Fibrosarcoma Tumorigenesismentioning
confidence: 99%
“…Beside expression levels, presentation on MHC molecules and strong stimulation of T cells against the antigen is mandatory. RHAMM induces specific T cell responses in different malignancies including AML . In peptide vaccination trials, the induction of a high frequency of specific T cell responses could be detected and also positive clinical results but no relevant clinical toxicity was detected after peptide vaccination against RHAMM .…”
Section: Discussionmentioning
confidence: 92%
“…RHAMM induces specific T cell responses in different malignancies including AML. 17,31,42 In peptide vaccination trials, the induction of a high frequency of specific T cell responses could be detected and also positive clinical results but no relevant clinical toxicity was detected after peptide vaccination against RHAMM. 21,27,31 We further analyzed .…”
Section: Discussionmentioning
confidence: 99%